External validation and clinical evaluation of the International Prognostic Score of Thrombosis for Essential Thrombocythemia (IPSET‐thrombosis) in a large cohort of Chinese patients. (17th February 2014) - Fu, Rongfeng; Xuan, Min; Lv, Cuicui; Zhang, Liyan; Li, Huiyuan; Zhang, Xian; Zhang, Donglei; Sun, Tiantian; Xue, Feng; Liu, Xiaofan; Liang, Haoyue; Zhang, Lei; et al.
Abstract Objectives In patients with essential thrombocythemia (ET), vascular complications contribute to both morbidity and mortality. To better predict the occurrence of thrombotic events, an International Prognostic Score of thrombosis for ET (IPSET‐thrombosis) was recently developed. We hereby presented an external validation and analysis of this model in a large Cohort of Chinese Patients. Methods We retrospectively evaluated the characteristics and risk factors for thrombosis in 970 Chinese patients with ET and estimated the clinical implications of the IPSET‐thrombosis model. Results The median follow‐up was 49 months (range, 0–360). Chinese ET patients had similar clinical characteristics as Caucasian patients. Similar to the IPSET‐thrombosis study, our multivariate analysis revealed age >60 (HR = 1.949), previous thrombosis (HR = 2.484), JAK2V617F mutation (HR = 1.719), and cardiovascular risk factors (HR = 1.877) as independent risk factors for thrombosis. We confirmed that the above risk factors in IPSET‐thrombosis, when compared with traditional risk factors (e.g., age ≥60 and previous thrombotic events), were more predictive of thrombotic events (C‐index 0.714 vs. 0.647). Classification by IPSET‐thrombosis risk groups revealed different cumulative thrombosis‐free survival (P < 0.001). For treatment, patients in the intermediate‐ and high‐risk group derived clinical benefit from cytoreductive agents (P < 0.05), but those in the low‐risk group did not (P = 0.446). The lower risk of thrombosis on cytoreductive therapy was related to decrease in leukocyte count during the disease course. Conclusions We validate the reproducibility of IPSET‐thrombosis in Chinese ET patients and provide key clinical implications.